Advancement of the Quantitative Blood Oxygenation Level-Dependent (qBOLD) MRI technique to improve clinical feasibility. - Alzaidi, Ahlam (2025)
Quantitative Blood Oxygenation Level Dependent (qBOLD) MRI offers a non- invasive method for measuring brain oxygenation, with potential applications in various neurological conditions. However, its clinical implementation has been hindered by methodological inconsistencies and challenges in standardisation. This thesis aims to address these obstacles and advance the clinical applicability of qBOLD techniques through three studies.